Disability Law in the Czech Republic: A Case Study - Sinecka, Jitka (Disability Studies Quarterly, 2007)
The Czech Republic has been in transition from communism to democracy since 1989. How disability has been defined and understood in Czech society is described in political, social and cultural context. The state of law and disability policy is illustrated by a case study involving a mother with a disabled son who had to be placed in an institution due to the lack of financial resources. The case is described as an insight into the current state of disability law and its interpretation in the Czech Republic. This case is examined as a human rights issue and it is argued that the transition from medical model and welfare law to a civil and human rights law, with regard to people with disabilities, has not yet been completed in the Czech Repulic.